2017
DOI: 10.1080/13816810.2017.1288825
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein polymorphisms in a Northern Spanish population with neovascular and dry forms of age-related macular degeneration

Abstract: The present study is the first to investigate the potential association of SNPs at MT genes with susceptibility to AMD. We found a significant association of SNP rs28366003 at MT2A gene with susceptibility to the dry form of AMD in a Northern Spanish population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…; García et al. ). In addition, numerous studies have revealed that this variant might influence treatment outcomes in patients with AMD (Dedania et al.…”
Section: Discussionmentioning
confidence: 97%
“…; García et al. ). In addition, numerous studies have revealed that this variant might influence treatment outcomes in patients with AMD (Dedania et al.…”
Section: Discussionmentioning
confidence: 97%
“…This action may be restricted if the polymorphism in the CFH gene changes the protein product while uncontrolled action of complement cascades is able to recruit inflammatory cells towards retina. Several studies have shown association of CFH gene especially Y402H variants with AMD in most ethnicities (Edwards et al 2005;Haines et al 2005;Klein et al 2005;Chowers et al 2008; Nischler et al 2011;Quan et al 2012;Soysal et al 2012;Garc ıa et al 2015;Hautam€ aki et al 2015;Hughes et al 2015). However, in some other ethnicities such as Koreans, CFH Y402H polymorphism was only shown to be marginally associated with the risk of developing AMD (Kim et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…We conducted the first study of that kind in Croatia and found that nearly 6 % of the healthy postpartum women were G allele carriers ( 4 ). Several authors reported higher percentages of G allele carriers in case study groups than controls ( 80 , 84 , 97 , 100 ), and others reported no differences ( 88 , 96 ). Higher frequency of AG genotype was reported among white (12.8 %) than black (2.1 %) women in the USA ( 98 ).…”
Section: Regulation Of Metallothionein Synthesis and Mt2a Polymorphismsmentioning
confidence: 99%
“…According to the literature data, the frequency of the AA genotype ranges from 84.0 % to 95.5 % in healthy Polish ( 80 , 81 , 82 , 84 , 85 , 86 , 87 , 88 ), 86.0 % to 90.4 % in Turkish ( 89 , 90 , 91 , 92 , 93 , 94 ), and about 82 % in Japanese population ( 95 , 96 ). The highest frequencies were found in a healthy Spanish population (97.9 %) ( 97 ), US black women (97.9 %) ( 98 ), Croatian women (93–94.0 %) (4, 99), and a healthy Chinese population (92.5 %) ( 100 ). The lowest frequency of 57.8 % and 53.4 % was found in healthy Iranian and Columbian populations, respectively ( 101 , 102 ).…”
Section: Regulation Of Metallothionein Synthesis and Mt2a Polymorphismsmentioning
confidence: 99%
See 1 more Smart Citation